Usaha Ulama Hadith Mutaqaddimin Dalam Mengekang Penyebaran Hadith Palsu - Muhammad Shamel Bin Abd Rahman; Amiruddin Mohd Sobali (2025)
E-Proceeding The9th International Conference on Nabawi Heritage(SWAN 2024) Theme: Prophetic Legacy in Development of Civil Society in the Era of Artificial Intelligence (AI) 6-7 November 2024